1980
DOI: 10.1136/jcp.33.5.488
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B8, immunoglobulins, and antibody responses in alcohol-related liver disease.

Abstract: SUMMARY Ninety-two British, caucasian, alcoholic patients with liver disease were grouped on the basis of hepatic histology into fatty change, hepatitis with or without cirrhosis, and cirrhosis alone. Men with alcoholic hepatitis with or without cirrhosis showed an increased incidence of the histocompatibility antigen HLA-B8 (P < 0-02). Increased measles antibody titres were found in patients with cirrhosis with or without hepatitis and were associated with the B8 phenotype in both sexes. Rubella antibody titr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 14 publications
1
19
0
1
Order By: Relevance
“…Autoantibodies were detected in ALD patients decades ago. The observed frequency in previous studies varied but overall it seemed to occur in 25–40% of the patients, which was significantly lower than that of ours (63.8%). This probably reflects the fact that with the in‐depth study of non‐viral chronic liver diseases, more clinicians have realized the immune mechanisms involved in the ALD and therefore more patients have undertaken this test.…”
Section: Discussionsupporting
confidence: 93%
“…Autoantibodies were detected in ALD patients decades ago. The observed frequency in previous studies varied but overall it seemed to occur in 25–40% of the patients, which was significantly lower than that of ours (63.8%). This probably reflects the fact that with the in‐depth study of non‐viral chronic liver diseases, more clinicians have realized the immune mechanisms involved in the ALD and therefore more patients have undertaken this test.…”
Section: Discussionsupporting
confidence: 93%
“…Clear evidence demonstrates that the liver alteration is induced by the toxic effects of ethanol (1). However, several abnormalities in the immune systems of alcoholic cirrhosis (AC) patients have been described (2)(3)(4)(5)(6)(7)(8)(9). The cellular and molecular bases of these immune alterations, as well as their pathogenic significance and clinical implications, remain unknown.…”
Section: -670)mentioning
confidence: 99%
“…This their pathogenic significance and clinical implications abnormality may be related to overproduction of IgA remain unknown. Hypergammaglobulinaemia, mainly and i™™ 6 disturbances in patients with alcoholic enhancement of the serum IgA concentration, is a comr dlsease · mon immunological finding in patients with alcoholic We have studied serum IgA, IgAl, IgA2 and IL-6 conliver cirrhosis (5)(6)(7). It has been demonstrated that this centrations in heavy alcohol drinkers without clinical high immunoglobulin concentration is not due to abnor-liver disease in comparison with alcoholic liver cirrhosis mal catabolism of IgA (1)(2).…”
Section: ) Peripheral Blood Monoclonal Cells Have Been Reportedmentioning
confidence: 99%
“…Abnormalities in the immune systems of alcoholic liver in P atients with alcoholic liver cirrhosis < 10 )· IL ' 6 Ρ ΓΟ ' cirrhosis patients have been described (1 -4). However, duction Correlates closely with IgA serum levels.…”
Section: ) Peripheral Blood Monoclonal Cells Have Been Reportedmentioning
confidence: 99%